Dynamic Status Signal Reflects Outcome of Social Interactions, but Not Energetic Stress - Tarvin, Keith A.; Wong, L. Jin; Lumpkin, David C.; Schroeder, Gabrielle M.; D'Andrea, Dominic; Meade, Sophie; Rivers, Pearl; Murphy, Troy G. (Frontiers in Ecology and Evolution, 2016)
Social defeat induces stress-responses in a wide array of vertebrates and can generate winner-loser effects. Dynamic condition-dependent signaling systems that reflect preparation for subsequent agonistic interactions, and thereby mediate winner-loser effects, should be more sensitive to competitive history than to non-social sources of stress. Bill color of female American goldfinches (Spinus tristus) is a dynamic condition-dependent ornament that functions as a signal of competitive status and mediates intrasexual agonistic social interactions. We tested the “social experience signaling hypothesis” in female goldfinches by (1) manipulating a non-social energetic stressor by experimentally elevating flight costs via wing-clipping in free-ranging birds, and (2) manipulating social experience by staging competitive interactions among captive birds. Bill color change did not differ between wing clipped and non-clipped females, even though stress-response, as measured by the heterophil to lymphocyte (H:L) ratio, increased significantly in clipped females relative to unclipped females. In contrast, winners and losers in the social experience experiment differed significantly in the degree and direction of bill color change following social contests, with bill color increasing in winners and decreasing in losers. These results suggest that dynamic bill color of female American goldfinches signals recent social history, but is less sensitive to some stressors stemming from non-social sources, and thereby suggest that signals can evolve sensitivity to specific types of processes relevant to the context in which they are used.